Experimental Study on the Change in Freezing Temperature During the Remediation of Pb-Contaminated Soils with Biochar - Shanbo Han; Wei Cao; Yaling Chou; Erxing Peng (Atmosphere)
In the remediation process of heavily metal-contaminated soil, biochar can change the ion content and soil structure, significantly impacting soil freezing. This experiment used freezing ambient temperature, water (W) content, heavy metal (M) contents, and biochar (BC) contents as factors affecting soil freezing. The test soil was manually compacted in a homemade acrylic device to achieve a compaction level of 90%. The temperature changes of the soil during low-temperature freezing were monitored through thermometry experiments. The results indicated that soil freezing temperature decreased with increasing heavy metal and biochar contents and increased with increasing initial water content and freezing ambient temperature. Multiple freeze–thaw cycles revealed the interaction between biochar and heavy metals. The effects of biochar on the freezing temperature of soil with different heavy metal contents were different; in the soil with the same heavy metal content, 3% biochar contents had little effect on the freezing temperature of heavy metal-polluted soil, and 5% and 7% biochar contents significantly improved the freezing resistance of the soil. Freeze–thaw cycling had little effect on the soil’s microporous structure, resulting in minimal changes in soil freezing temperatures after seven cycles. Correlation analyses of heavy metals, water content, and biochar revealed that the effects of these factors on freezing temperature were in the order of heavy metals > water > biochar. The composite freezing temperature of biochar and heavy metal overlaps well. The initial freezing temperature of the soil was used to predict the unfrozen water in the soil. The prediction results showed that biochar increased the content of unfrozen water in the soil.